POWER DOPPLER IMAGING IN PATIENTS WITH SUSPECTED PROSTATE CANCER - T. V. Shatylko; L. N. Sedova; A. Yu. Korolev (Вестник урологии)
Abstract. This study was aimed to evaluate the role of power Doppler imaging in diagnosis of prostate cancer and prediction of its aggressiveness. This study included 118 patients with prostate cancer suspected due to elevation of prostate specific antigen (PSA) values to > 4.0 ng/ml. All patients underwent transrectal prostate biopsy with ultrasound guidance for histological verification. Prostate was scanned in power Doppler mode and one of vascularization patterns was assigned, as described by Zhao et al. Power Doppler imaging results and biopsy results were compared. Forty eight patients had normal results of power Doppler imaging. Fifty five patients had focal enhancement of blood flow, which allowed to perform a targeted biopsy of suspected lesion. Fifteen patients had diffusely enhanced blood flow. Sensitivity of power Doppler imaging was 82.4%, specificity was 70.5%, positive and negative predictive values were 66.7% and 72.3% correspondingly. Overall accuracy for prostate cancer detection was 81.1%. Association between observed vascular patterns and Gleason score, tumor dissemination and PSA level was detected. Power Doppler imaging allows efficient detection, staging and prediction of aggressiveness of prostate cancer, when compared to standard transrectal ultrasound imaging.